Correlation of electrical resistivity with some soil parameters for the development of possible prediction of slope stability and bearing capacity of soil using electrical parameters - Osman, S.B.S. (Universiti Putra Malaysia Press, 2014)
The long term objective of this research is to look into the possibility of replacing soil strength parameters such as cohesion and angle of friction with electrical resistivity value for the purpose of computing among others, factor of safety in slopes or bearing capacity of soil. This paper however is limited to the investigation of correlation between electrical resistivity with some selected soil parameters. Electrical resistivity tests, using a basic multi meter, steel moulds and other related equipment, were conducted in the laboratory on soil samples with variations in soil type, compaction energy and moisture content. The samples consisted of predominantly clay, silt and sandy size particles and were compacted in a 100 x 100 mm square mould, while the corresponding electrical resistivity tests were carried out using the disc electrode method in accordance to BS 1377. The values of the electrical parameters such as voltage, current and resistance, with the corresponding value of soil parameters such as cohesion, angle of friction and moisture content, were measured and recorded. The results of the tests produced some initial crude relationships between electrical resistivity and the selected soil parameters. The strongest correlation between electrical resistivity and angle of internal friction, Ï, was obtained from the clay size samples with R2 of 0.824, while the maximum correlation between electrical resistivity and moisture content again was obtained through the clay samples with R2 of 0.818. From the other results and graphs analyzed, some consistencies and specific trends of behaviour observed gave some early indications that a more detail and precise correlation between electrical resistivity and soil strength parameters could be very well possible in future. Â© 2014 Universiti Putra Malaysia Press.